Effects of Fermented Feed on the Growth Performance, Intestinal Function, and Microbiota of Piglets Weaned at Different Age - Liu, Shuai; Xiao, Hao; Xiong, Yunxia; Chen, Jingping; Wu, Qiwen; Wen, Xiaolu; Jiang, Zongyong; Wang, Li (Frontiers in Veterinary Science, 2022)
The beneficial function of fermented feed in livestock industry has been widely investigated. However, little is known about the effects of fermented feed on different weaned-day piglets. This study aimed to investigate the effects of fermented diet on the growth performance, intestinal function and microbiota of piglets weaned at age of 21 days and 28 days. The results found that weaning on d 21 significantly increased (P < 0.05) ADG, and ADFI (calculated based on wet weight and dry matter), while reduced (P < 0.05) F: G, the activities of trypsin and lipase of jejunum and villus height of ileum, compared with 28-d weaning. The protein levels of Occludin, Claudin-1, ZO-1 of ileum in the groups weaning on d 21 were less (P < 0.05) than the groups weaning on d 28. Moreover, dietary supplementation with fermented diet upregulated (P < 0.05) Occludin, Claudin-1, ZO-1 proteins of ileum, compared with the groups treated with control diet both weaning on d 21 and d 28. In addition, dietary supplementation with fermented diet decreased (P < 0.05) the relative abundance of Clostridia (class) and increased (P < 0.05) Bacteroidia (class) level of cecal microbiota, compared with the groups treated with control diet both weaning on d 21 and d 28. However, supplementation with fermented diet did not affect the concentrations of short-chain fatty acids in the cecum (P > 0.05). Therefore, our data suggest that feed digestibility is improved in piglets weaned at 21 days, but intestinal barrier function is weaker than in piglets weaned at 28 days. However, compared with feeding control diet, supplementation with fermented diet both improved feed conversion and intestinal barrier function of weaned piglets by modulating intestinal microbiota.